الخصائص الديمغرافية والصحية والبدنية والعزو السببي لمتعاطي المخدرات والعقاقير المهلوسة في مراكز الإصلاح والتأهيل الأردنية - العرجان، جعفر فارس عبدالرحيم; العلوان، بشير أحمد; الكفاوين، أحمد ابراهيم محمود (جامعة الكويت - مجلس النشر العلمي, 2015)
هدفت هذه الدراسة إلى تعرف الخصائص الديمغرافية والبدنية والصحية لدى الأفراد المتعادلين للمخدرات والعقاقير المهلوسة من نزلاء مراكز الإصلاح والتأهيل في الأردن، ومقارنتها مع مجموعتين (من غير المتعاطين، ومن ممارسي النشاط البدني من أجل الصحة)، وأكثر أنواع المخدرات والعقاقير المهلوسة والمذيبات الطيارة تعاطيا، والأسباب التي دفعت المتعاطين للتعاطي، والفروق في مركز العزو السببي للنجاح والفشل بين المجموعات الثلاث، والعلاقة بين ممارسة رياضة بناء الأجسام وتناول الاستيرويدات البنائية وتعاطى المخدرات. تكونت عينة الدراسة من ثلاث مجموعات، هي: متعاطو المخدرات والعقاقير المهلوسة، الموجودون في مراكز الإصلاح والتأهيل الأردنية وعددهم (116) فردا، والمجموعة الثانية: من غير المتعادلين للمخدرات، الموجودين في مراكز الإصلاح والتأهيل الأردنية بتهم لا تتعلق بتعاطي المخدرات وعددهم (54) فردا، والمجموعة الثالثة: من الأفراد الممارسين للنشاط البدني بهدف تعزيز الصحة العامة ومن ليس لهم أية سوابق جرمية، وعددهم (226) فردا. طبقت على عينة الدراسة — بمجموعاتها الثلاث — استبانة تقيس الخصائص الديمغرافية، والصحية والبدنية لهم، إضافة إلى تطبيق مقياس العزو السببي للنجاح والفشل، المصمم من قبل (1975 Rotter). أشارت النتائج إلى وجود فروق إحصائية دالة في اتجاه العزو السببي للنجاح والفشل بين المجموعات الثلاث؛ حيث تميز الأفراد الممارسون للنشاط الرياضي من أجل الصحة بارتفاع اتجاههم نحو العزو السببي الداخلي بنسبة وصلت إلى (63.71%)، في حين اتجه ما نسبته (13.27%) نحو العزو السببي الوسيطى، فيما كانت نسب التوجه نحو العزو السببى الخارجي لدى الأفراد المتعاطين للمخدرات والعقاقير المهلوسة (99.13%، وما نسبته (0.86%) نحو العزو السببي الوسيطي، وعدم وجود أي فرد منهم ضمن العزو السببي الداخلي، قياسا إلى ما نسبته (83.33%) كانوا متوجهين نحو العزو السببي الخارجي، وما نسبته (16.66%) نحو العزو السببي الوسيطي، وعدم وجود أية نسبة في التوجه نحو العزو السببي الداخلي، وذلك لدى الأفراد نزلاء مراكز الإصلاح والتأهيل من غير المدمنين، وإلى وجود علاقة بين تعاطي المخدرات والعقاقير المهلوسة من جهة، وزيادة نسبة انتشار التدخين وتناول الكحول من جهة أخرى، وبين تناول الاستيرويدات البنائية وممارسة لعبة بناء الأجسام، وفي ضوء ذلك يوصى بضرورة زيادة الرقابة الأمنية والصحية على المراكز الرياضية الصحية للتأكد من عدم ترويج الاستيرويدات البنائية بين المشاركين، كما يوصي الباحثون بضرورة إدخال العلاج النفسي وتفعيله ضمن خطة العلاج للأفراد المدمنين على المخدرات والعقاقير المهلوسة لرفع مستوى الحالة النفسية وزيادة مستوى الثقة بالنفس لديهم؛ لمساعدتهم على التغلب على ظروفهم وعدم العودة إلى الإدمان.
The study aimed to identify the demographic characteristics and physical health of individuals drug users and drug hallucinogenic guests Centers study aimed to identify demographic characteristics and physical health of individuals drug users and drug hallucinogenic guests reform and rehabilitation centers in Jordan, and compared with the two groups (non- drug users, and practitioners physical activity for health), the most common types of drugs and drug hallucinogenic and solvents Flyer abused, and the most important reasons why drug abusers to abuse, and the differences in the center of attribution causal for success and failure among the three groups, and on the relationship between sport body building and eat steroids structural and drug abuse. The study sample consisted of three groups: drug users and drug hallucinogenic number (116) personnel, who are in correctional and rehabilitation centers of Jordan, and the second number (54) individuals, non- drug users, and who are in correctional and rehabilitation centers of Jordan on charges not related to drug use, and the third group number (226) individuals, individuals practitioners of physical activity in order to promote public health and do not have any criminal record. The results indicated the existence of differences in statistical function in the direction of attribution causal for success and failure among three groups, where the excellence of individuals practicing sports activity for health high proportion of their direction towards the attribution causal procedure by up to (63.71%), in terms of turn accounted for (13.27%) about attribution causal catalysed, while the ratios trend towards attribution causal external individuals drug users and drug hallucinogenic (99.13%), and the rate of (0.86%) towards the attribution causal catalysed, and the absence of any individual of them within the attribution causal procedure, compared to a rate of (83.33%) were heading towards the attribution causal external, and of (16.66%) towards the attribution causal catalysed and the absence of any rate in the trend towards attribution causal procedure and that the individuals guests reform and rehabilitation centers of non- addicts, and to the existence of a relationship between drug abuse and drug hallucinogenic on the one hand and between the increase in the prevalence of smoking and alcohol intake, and between taking steroids Constructivism and the practice of building game objects, in the light, it is recommended the need to increase security surveillance and health centers, sports health to make sure that promote steroids Constructivism among the participants, also recom¬mends that researchers need to enter treatment psychological and activated within the plan of treatment for individuals addicted to drugs and hallucinogenic drugs to raise the level of mental state and increase the level of self - confidence they have to help them overcome and not return to addiction.
Keywords: المخدرات -- العقاقير المهلوسة -- نظرية العزو السببي -- مراكز الإصلاح والتأهيل -- الأردن